Corporate social responsibility in Malaysia: its practice and its concern on environmental protection / Nurul Ikhlasmurni Ahmad, Zaneella Zainudin and Nur Amalina Badroldin. - Ahmad, Nurul Ikhlasmurni; Zainudin, Zaneella; Badroldin, Nur Amalina (Faculty of Law, 2008)
This research studies the role played by Corporate Social Responsibility practices in Malaysia. The aims of this research are to look at the application and implementation of Corporate Social Responsibility (CSR) in Malaysia and whether corporations in Malaysia practice CSR in their company. Environmental protection is the agenda of both the United Nation (UN) and the World Trade Organization (WTO) in all practices therefore it is also an important issue in CSR. This research also tries to look at the strengths and weaknesses of the CSR in Malaysia. There are many corporations that practices CSR in Malaysia i.e. Telekom Malaysia, TNB, Gardenia Malaysia, Tesco Malaysia, Microsoft Malaysia, Standard Chartered Bank Bhd, PIDM, Ikea, to name a few. CSR is not an authority; it is just a responsibility to practice. In this research, the data was gathered from interviews, reviews on some literature sources that have been published previously by accredited scholars and researchers, reported and unreported cases and the recent issues concerning the CSR. Thus, this study recommends that the government should make CSR as obligatory to every corporation in order to help in enhancing the standard and knowledge of the corporation in Malaysia especially with reference to environmental protection through sustainable development.